CHARACTERISTICS OF URETEROVAGINA FISTULA PATIENTS AT HASAN SADIKIN HOSPITAL BANDUNG IN 2017 -2021 - Helmi, Kiki; Tjahjodjati (Indonesian Journal of Urology, 2025)
Objective: The study aims to determine the characteristics of ureterovaginal fistula patients at Hasan Sadikin Hospital in Bandung for the 2017-2021 period. Material & Methods: This research was conducted using a descriptive method with a cross-sectional approach. The inclusion criteria in this study were all patients who experienced ureterovaginal fistula and underwent surgery at Hasan Sadikin Hospital. Exclusion criteria in this study were incomplete patient data until the variables studied did not exist. Results: From a total of 35 people who experienced ureterovaginal fistula the most in 2020 were 7 people (23.3%). The mean age was 39.93 ± 11.26 years, the longest distance to surgery was 10.17 ± 9.56 months, and duration of hospitalization 7.31 ± 5.45 days. The highest percentage of age who experienced ureterovaginal fistula was 36-45 years as many as 3 people (30%). Based on the etiology, the most common was supravaginal hysterectomy as many as 5 people (45.5%). The most frequently performed procedure in this study was ureteroneocystostomy with a percentage of 65%. Conclusion: The most common cases of ureterovaginal fistula in 2017 to 2021 were in 2020, the most common age for experiencing ureterovaginal fistula was 36-45 years of age and the most common etiology was supravaginal hysterectomy. Keywords: Ureterovaginal fistula, characteristics, Hasan Sadikin Hospital